2019
DOI: 10.1002/oby.22412
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Follow‐up of the Mind Your Health Project: Acceptance‐Based versus Standard Behavioral Treatment for Obesity

Abstract: Objective In the Mind Your Health Trial, acceptance‐based behavioral treatment (ABT) for obesity outperformed standard behavioral treatment (SBT) at posttreatment. This trial compared effects over 2 years of follow‐up. Methods Participants with overweight or obesity (n = 190) were randomized to 25 sessions of SBT or ABT over 1 year and assessed at months 12 (i.e., posttreatment), 24 (1 year posttreatment), and 36 (2 years posttreatment). Results Weight‐loss differences previously observed at 12 months attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…This could be a valid promising result supporting the application of ACTbased intervention for individuals with obesity. Further studies are required to address the validity of such interventions, but some evidence has been already collected (Forman et al, 2013(Forman et al, , 2016(Forman et al, , 2019Cattivelli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This could be a valid promising result supporting the application of ACTbased intervention for individuals with obesity. Further studies are required to address the validity of such interventions, but some evidence has been already collected (Forman et al, 2013(Forman et al, , 2016(Forman et al, , 2019Cattivelli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mindfulness-based interventions have been shown to reduce weight-related eating psychopathology, such as binge eating [35,41], as well as to reduce high calorie food intake following exposure to appetitive cues [42]. Indeed, there are now several mindfulness-based interventions for the treatment of disordered eating, including Acceptance and Commitment Therapy for Binge Eating Disorder and obesity [43][44][45], and Mindfulness-Based Eating Awareness Training (MB-EAT) [46][47][48]. Given the benefits of mindfulness practices for eating psychopathology, it is possible that these practices may be effective for improving other aspects of eating behavior, including dietary quality.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Mind Your Health II Project (MYH II), a larger and longer (1 year) RCT, demonstrated that ABT produced greater 12-month weight loss than did the SBT treatment (13.3 vs. 9.8%), again when conducted by experienced clinicians 39 . In the long-term post-treatment follow-up data from MYH II 40 , weight loss at 24-months (7.5 vs. 5.6%; P = 0.15) or at 36 months (4.7 vs. 3.3%; P = 0.31) did not significantly differ between ABT and SBT groups. However, among treatment completers who attained at least 10% body weight loss during the intervention, those receiving ABT were almost twice as likely to retain at least 10% body weight loss at two-year followup (31.6 vs. 17.1%; P = 0.04).…”
Section: Standard Behavioral Interventions Are Foundational For Diabementioning
confidence: 80%
“…Two randomized controlled trials (RCTs) have demonstrated significantly greater weight losses for ABT compared to SBT 39,40 . The Mind Your Health Project, a 40-week RCT comparing ABT to SBT, demonstrated that ABT resulted in significantly higher weight loss than SBT at post-treatment (13.2 vs. 7.5%) and at 6-month followup (11.0 vs. 5.0%) in a post-hoc analysis when the intervention was administered by weight-control experts 41 .…”
Section: Standard Behavioral Interventions Are Foundational For Diabementioning
confidence: 99%